Proceedings of the 9th International Conference on Multimodal Interfaces 2007
DOI: 10.1145/1322192.1322218
|View full text |Cite
|
Sign up to set email alerts
|

Gaze-communicative behavior of stuffed-toy robot with joint attention and eye contact based on ambient gaze-tracking

Abstract: This paper proposes a gaze-communicative stuffed-toy robot system with joint attention and eye-contact reactions based on ambient gaze-tracking. For free and natural interaction, we adopted our remote gaze-tracking method. Corresponding to the user's gaze, the gaze-reactive stuffed-toy robot is designed to gradually establish 1) joint attention using the direction of the robot's head and 2) eye-contact reactions from several sets of motion. From both subjective evaluations and observations of the user's gaze i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(38 citation statements)
references
References 19 publications
3
35
0
Order By: Relevance
“…Yoshikawa et al [45] demonstrated that robot's responsive gaze, either following or avoiding its human partner's gaze direction, can give people a stronger feeling of being looked at than non-responsive gaze cases. Yonezawa et al [44] found that a stuffed-toy robot's joint attention gaze and eye contact with a human partner elicited a favorable feeling towards the robot. Our work provides empirical evidence that carefully planned robot gaze cues can significantly affect participants' task performance and subjective experience during robot-to-human handovers.…”
Section: Robot Gaze In Hrimentioning
confidence: 99%
“…Yoshikawa et al [45] demonstrated that robot's responsive gaze, either following or avoiding its human partner's gaze direction, can give people a stronger feeling of being looked at than non-responsive gaze cases. Yonezawa et al [44] found that a stuffed-toy robot's joint attention gaze and eye contact with a human partner elicited a favorable feeling towards the robot. Our work provides empirical evidence that carefully planned robot gaze cues can significantly affect participants' task performance and subjective experience during robot-to-human handovers.…”
Section: Robot Gaze In Hrimentioning
confidence: 99%
“…Interestingly, in HRI, Yonezawa et al showed that the eye contact with a stuffed-toy robot, induced a favorable evaluation of the robot [26]. In another study, in which humans were teaching a robot, it seemed more intentional when it displayed eye contact compared to a random gaze [27].…”
Section: Introductionmentioning
confidence: 99%
“…These features are applicable for estimating user attention and targets of interest in daily life using user gaze information and offering proper information/contents for each user [12]. Moreover, the features enable us to provide a gaze-reactive robot for evoking communication for people who have lost the desire to communicate due to dementia or trauma [15]. In the "Gazecoppet" system ( Figure 13), a stuffed-toy robot reacts to gazecommunicative interaction by expressing its gazing behaviors as if looking at an object.…”
Section: Discussionmentioning
confidence: 99%
“…In the "Gazecoppet" system ( Figure 13), a stuffed-toy robot reacts to gazecommunicative interaction by expressing its gazing behaviors as if looking at an object. Corresponding to the gazetracking results, the robot reacts in the following two ways: i) joint attention, which means "looking at the same object" expressed by facing the direction when the user looks around the robot; and ii) eye-contact reaction by voices and gestures when the user gazes at the robot [15]. The system decides which reaction the robot should manifest and synthesizes its motion and/or voice corresponding to the reaction type.…”
Section: Discussionmentioning
confidence: 99%